Ocean Acidification and Multilateral Environmental Agreements - Naporn Popattanachai; Elizabeth Kirk (2021)
Ocean acidification is caused by increased absorption of carbon dioxide (CO2). Since the beginning of the industrial age there has been an increase of around 30 per cent in the acidity of ocean surface waters. Given that the cause is limited to CO2 emissions, there are relatively few multilateral environmental agreements (MEAs) that are relevant to the control of ocean acidification. Some, such as the Desertification Convention, are relevant in that the land-use management practices promoted under the Convention may help improve both the ability of certain areas to act as sinks and to prevent the release of CO2 as a result of poor land management. Others are more directly relevant. The United Nations Convention on the Law of the Sea (UNCLOS) addresses marine pollution from land-based sources (Article 207) and through the atmosphere (Article 212). The United Nations Framework Convention on Climate Change (UNFCCC) and the regime built upon it addresses emissions of greenhouse gases (GHGs), including CO2. Others, such as the Convention on Biological Diversity, (CBD) are relevant in that they address the impact of ocean acidification on marine species.In this chapter we focus on three key MEAs—UNCLOS, the UNFCCC regime and the CBD—and the relationship between them. As we demonstrate, the UNFCCC and UNCLOS are, or at least should be, inextricably linked in combating ocean acidification. The CBD is focussed on impacts on marine species and has been proactive in addressing ocean acidification and bringing the need for action to the attention of the UNFCCC. The formal links between the three regimes are not, however, as strong as they ought to be to tackle ocean acidification, and so we assess the suitability of potential mechanisms to strengthen these links.